2017
DOI: 10.1111/jgh.13644
|View full text |Cite
|
Sign up to set email alerts
|

Using transient elastography to predict hepatocellular carcinoma recurrence after radiofrequency ablation

Abstract: Findings of this study suggest that LS measurement using TE can be a useful predictor of HCC recurrence after RFA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…LS measured by two-dimensional shear-wave elastography has been reported as a significant predictive factor for OS after RFA for HCC 29 . However, in other studies in Korea, LS measured by TE or ARFI elastography did not have effective prediction performance for OS in HCC patients who received RFA 12,18 . In our study, we identified that an ARFI velocity cut-off value of 1.5 m/s for LS could significantly predict the OS of patients who underwent RFA for HCC.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…LS measured by two-dimensional shear-wave elastography has been reported as a significant predictive factor for OS after RFA for HCC 29 . However, in other studies in Korea, LS measured by TE or ARFI elastography did not have effective prediction performance for OS in HCC patients who received RFA 12,18 . In our study, we identified that an ARFI velocity cut-off value of 1.5 m/s for LS could significantly predict the OS of patients who underwent RFA for HCC.…”
Section: Discussionmentioning
confidence: 69%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ (including tumor size, number, tumor cell differentiation, vascular invasion, extra-hepatic metastasis, and serum AFP level), liver functional reserve (such as serum albumin level, platelet count, and portal hypertension), and field factors in the background liver (including the grade of hepatic inflammation and steatosis and the stage of liver fibrosis) 12,18,[25][26][27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 576 were excluded by screening titles and abstracts (because they were either conference abstracts, letters, reviews, case reports or irrelevant studies), leaving 26 potentially relevant full-text articles. Eventually, eight studies [11][12][13][14][15][16][17][18] with a total of 1276 patients, were included in this meta-analysis. One of the included studies (Yoon et al [18]) compared the predictive value LSM evaluated by ARFI elastography versus TE; we treated this article as two separate studies -'Yoon 2018 AFFI' and 'Yoon 2018 TE'.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…LSM is also found useful to predict de novo recurrence after curative treatment (e.g. resection or radiofrequency ablation) for HCC.…”
Section: Physical Modalitiesmentioning
confidence: 99%